Perdagangan Organ Tubuh Manusia untuk Kebutuhan Medis dalam Konteks Kejahatan Transnasional - Muhammad Aswar Basri (Faculty of Law, Universitas Airlangga, 2024)
This research focuses on the discussion of regulations in the field of health and transnational crime in responding to the rampant criminal acts of human organ trafficking carried out across countries. This research provides a limitation that the organ trade in question is for medical needs such as donors or transplants. The purpose of this study is to determine the existing criminal law and health law arrangements in Indonesia as well as the legal relationship between Indonesia and other countries regarding human organ trafficking in the context of transnational crimes. This study also provides appropriate legal and health efforts in tackling the rampant cases of human organ trafficking for medical needs carried out across countries. The research method used in this study is normative legal research with a statutory approach, literature review, and interviews with resource persons.